PENGARUH KOMITMEN ORGANISASIONAL AFEKTIF, BERKELANJUTAN, NORMATIF DAN BUDAYA ORGANISASIONAL TERHADAP KINERJA GURU - Nugrohowati, Mariana; Susilowati, Yeye (Jurnal Ilmiah Telaah Manajemen, 2019)
The reseach analyzed the impact of organizational commitment (affective, continuance, normative) and organizational culture on teacher job performance. The research sample were teachers of Sub Rayon 02 Private Senior High School in Semarang. The technique of sample drawing was proportional random sampling. The zise of sample by using was Slovin formula.Data were collected by the using questionnaire. The number of the data which able to analize were 186 respondents. The technique of data analysis was linear regression. This research results several findings (1) affective organizational commitment does not give influence to teacher job performance, (2) continuance organizational commitment is significant and gives negative influence to teacher job performance, (3) normative organizational commitment is significant and gives positif influence to teacher job performance, (4) organizational culture is significant and gives positive influence to teacher job performance. Keywords : affective organizational commitment, continuance organizational commitment, normative organizational commitment, organizational culture, job performance.